PEMBERDAYAAN PETANI RUMPUT LAUT DI KAMPUNG SARAWANDORI DISTRIK KOSIWO KABUPATEN KEPULAUAN YAPEN - Mohammad Rifa'i; Sheryl Viola A. Kirihio (ipdn, 2020)
The potential for marine products in the Yapen Islands is very abundant, including seaweed. However, it should be noted that coastal communities who work as seaweed farmers with all their limitations also face several problems, including limited knowledge and skills in seaweed cultivation, use of simple tools (raft method), traditional/hereditary cultivation methods, and the marketing of crops, whose reach is still limited. For this reason, the Regional Government through the Marine and Fisheries Service provides support and assistance in the context of empowering seaweed farmers. The purpose of writing this is to find out the process of empowering seaweed farmers in Sarawandori Village. Else, to explore the obstacles and supporting factors of the empowerment. This research used a qualitative research method with a descriptive approach. The results showed that the empowerment of seaweed farmers had been running even though the results were not optimal. For this reason, the government through the Yapen Islands Regency Maritime Affairs and Fisheries Office seeks to help farmers in the seaweed cultivation process, and facilitate farmers to be able to use more sophisticated technology and expand the marketing reach of seaweed and its processed products from Sarawandori Village to outside the Yapen Islands. Keywords: Empowerment, Seaweed, Farmer, Yapen Regency